2021
DOI: 10.1177/03000605211001984
|View full text |Cite
|
Sign up to set email alerts
|

New score for prediction of morbidity in patients undergoing open pancreaticoduodenectomy

Abstract: Objective The Physiological and Operative Severity Score for the enUmeration of Mortality and morbidity (POSSUM) is commonly used to predict the risk of postoperative complications in general surgery. However, use of the POSSUM is not absolutely suitable for open pancreaticoduodenectomy (OPD), which has unique complications such as pancreatic fistula formation. This study was performed to establish a new risk score for assessing the incidence of postoperative complications of OPD. Methods This retrospective ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 28 publications
(41 reference statements)
0
5
1
Order By: Relevance
“…Severe complications occurred more often in the development cohort, namely 33%. In our study the severe complication rate was 28.9%, which is lower than other studies [ 1 , 23 ]. Assessment of the model’s performance parameters resulted in a C-index of 0.67, a regression slope of 0.37, an intercept of 0.13, a Brier score of 0.25, and a scaled Brier score of <0.001.…”
Section: Discussioncontrasting
confidence: 79%
See 4 more Smart Citations
“…Severe complications occurred more often in the development cohort, namely 33%. In our study the severe complication rate was 28.9%, which is lower than other studies [ 1 , 23 ]. Assessment of the model’s performance parameters resulted in a C-index of 0.67, a regression slope of 0.37, an intercept of 0.13, a Brier score of 0.25, and a scaled Brier score of <0.001.…”
Section: Discussioncontrasting
confidence: 79%
“…Likewise, no clear classification was provided in terms of severe complications and their definitions. The risk model for complications established by Chen L et al also involves pancreatic texture as an intra-operative variable, and it is graded subjectively during the operation [ 1 ]. Clavien–Dindo of II or higher was considered significant, whereas most studies reported in the literature use alternative cut-offs (IIIa, IIIb, or higher) [ 2 , 4 , 8 , 23 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations